Failures of sewer pipes made of PVC / Ушкодження каналізаційних каналів виконаних з ПВХ труб - Kuliczkowska, Emilia; Gierczak, Maria (Видавництво Львівської політехніки, 2013)
This paper presents the field measurements results of sewer pipes made of PVC, which were newly laid in the ground. The research was carried out applying CCTV (Closed Circuit Television) inspections, which was performed during the construction works acceptance of the sewer pipes some weeks or months after their laying in the ground. More than 11 km of sewers from 11 cities in Poland were analyzed. The analysis was carried out based on the research conducted among other things by Kielce University of Technology. A detailed analysis of specific flexible pipes failures was carried out. Failures, which occurred most frequently and on the highest percentage of the sewer pipe lengths were identified. The failures were classified according to the intensity of their occurrence and caused danger. Class 1 covers the greatest failures and the highest level of danger, class 5 covers minor failures with the lower level of danger. The technical condition of the investig ated sewers was assessed by classifying the particular sections to one of 3 groups: G 1 – without failures, G 2 – with failures in 5th class, G 3 – with failures in classes 1st- 4th. The most probable reasons for failures were presented. Подано результати досліджень каналізаційних каналів з ПВХ труб, нещодавно прокладених в землі. Дослідження проведені за допомогою відеоспостереження (Closed Circuit Television, CCTV), що було виконане протягом прийому каналів перед початком їх експлуатації. Проаналізовано понад 11 км каналізаційних каналів в 11 містах Польщі. Аналіз виконано на підставі досліджень, зокрема Політехнікою Свентокшискою м. Кельце. Детально проведено аналіз специфічних ушкоджень для гнучких труб, а також ушкоджень, що найчастіше зустрічаються для значного процента по довжині досліджуваних каналів. Пошкодження поділено на п’ ять класів в залежності від інтенсивності їх прояву і від величини створеної ними загрози. Перший клас характеризує найбільше пошкодження і найвищий ступінь загрози, а п’ятий – найменше пошкодження з найнижчим ступенем загрози. Виконано оцінку технічного стану досліджуваних каналізаційних каналів шляхом класифікації окремих відрізків до однієї з трьох груп: G1 – без ушкоджень, G2 – з ушкодженнями п’ ятого класу, G3 – з ушкодженнями І-IV класів. Вказані можливі причини виникнення тих ушкоджень.
Keywords: sewers; CCTV inspections; PVC pipes failures; каналізація; CCTV інспекція; аварії труб з ПВХ